Immediate effects of high-intensity laser therapy for nonspecific neck pain: a double-blind randomized controlled trial - Xie, Yuhua; Diao, Yingxiu; Wu, Dongyu; Liao, Manxia; Liao, Linrong (Frontiers in Medicine, 2025)
ObjectivesThe objective of this research was to assess the immediate effects of high-intensity laser therapy (HILT) on nonspecific neck pain (NNP) by evaluating outcome measures such as pain intensity, cervical active range of motion (ROM), stiffness of neck muscles, and functional disability.MethodsThis clinical trial, which was conducted in a double-blind and randomized manner, involved patients diagnosed with NNP who were allocated either to either a HILT group (HILT + exercise) or a placebo group (placebo-laser therapy + exercise). The primary outcome measures encompassed pain intensity via the visual analogue scale (VAS), cervical active ROM, stiffness of neck muscles (splenius capitis, semispinalis capitis, and neck fascia), as well as functional disability via the neck disability index (NDI). Statistical evaluations were carried out using SPSS version 25.0, with a significance threshold established at p < 0.05.ResultsA total of 28 individuals diagnosed with NNP were randomly allocated to either the HILT group (n = 14) or the placebo group (n = 14). Upon initial comparison, no significant differences (p > 0.05) were observed between the two groups. After treatment, both groups showed notable improvements in all outcome measures compared to baseline (p < 0.05); moreover, the HILT group demonstrated greater efficacy compared to the placebo group in terms of VAS scores (29.64 ± 8.43 mm, p = 0.001), cervical lateral flexion (right 22.46 ± 3.62°, p = 0.011; left 22.34 ± 2.74°, p = 0.034) and neck muscle shear modulus (splenius capitis muscle 22.48 ± 4.03 kPa, p = 0.001; semispinalis capitis muscle 23.50 ± 5.59 kPa, p = 0.028); however, no statistically significant differences (p > 0.05) were identified between the groups in cervical flexion, extension, rotation, neck fascia stiffness and NDI scores.ConclusionHILT has immediate efficacy for NNP and may be considered as one of the alternative interventions for NNP.Clinical trial registrationhttp://www.chictr.org.cn/, identifier ChiCTR2200061008.